Prenez sur moi vostre exemple: The ‘clefless’ notation or the use of fa-clefs in chansons of the fifteenth century by Binchois, Barbingant, Ockeghem and Josquin - Woetmann Christoffersen, Peter (Danish Yearbook of Musicology, 2010)
Ockeghem’s famous canon ‘Prenez sur moi’ is in most scholarly publications classifi ed as member of an exclusive group of ‘clefless’ compositions, which uses combinations of flats in all or some of its voices to organize pitch structures. However, while these songs do not use the conventional ‘letter clefs’ to specify the pitch, they are certainly not ‘clefless’, since the flats or rather the fa-signs, which refer to contemporary hexachordal theory, carry out some of the functions of the normal clefs, and it is thus most productive to regard them as using ‘fa-clefs’. The article investigates the use of fa-clef notation in chansons by Barbingant (‘L’omme banny’), Binchois (‘Comme femme desconfortee’, ‘Mon seul et souverain desir’, and most likely also by Binchois ‘Tous desplaisirs’), Guillaume le Rouge (‘Se je fais duel’), and related songs in the chansonnier Pavia 362 and the Schedelsches Liederbuch, with the aim of outlining some answers to the question of why such notation was used. Two models of structuring arrays of fa-clefs are discerned: 1) the most common is a formation of alternating fi fths and fourths, which interlocks in the voices; and 2) a corresponding arrangement of interlocking fifths only, which means that at least one voice will need a key signature of one flat or one sharp more than the other voices. The theories of pitch indeterminateness adhered to by most scholars hold true, but the investigation shows that the situation turns out to be a bit more complicated than that. In addition to allowing performances of indeterminate pitch as such the fa-clefs may have had functions as means 1) to indicate alternative performing pitches a fifth apart by exchanging sets of (imagined) letter clefs; 2) to allow the notation of songs, which needed a key signature of one sharp in the uppermost voice (limited to formations of fifths only, probably a speciality of Binchois); and 3) to make shorthand notation for letter clefs in compositions with two- or three-flat signatures. While it is quite possible that the common music scribe’s knowledge of the meaning and advantages of the fa-clef notation was waning around the middle of the 15th century, Ockeghem certainly knew all its secrets. With ‘Prenez sur moi’ he reduced the concept to essentials and used it to develop or signal a new technique of diatonic canon which is presented emblematic in its canon at the fourth and at the seventh. Also, it is remarkable how easily fa-clefs operate the different possible modes in a performance of Ockeghem’s Missa Cuiusvis toni. If arrays of fa-clefs are imagined when performing from the notation of the Chigi Codex, all three modes can be performed within the same general tessitura. Later Josquin Desprez erected a monument for Ockeghem in his setting of Jean Molinet’s lament ‘Nimphes des bois’ for fi ve voices by using fa-clefs, black notes, and a canon prescription.